(untitled) (Journal of Society of Surgeons of Nepal, 2016)
Prof. Dr Rajesh N Gongal ,FRCS (Eng) returned to Nepal from UK completing his surgical training in 1998 and has been working in Patan Hospital, initially as a Consultant and then as a Medical Director. Following the establishment of Patan Academy of Health Sciences (PAHS), he was appointed the Founding Dean of School of medicine. At present, he serves as the Rector of PAHS. He also served as the Chief Editor of Journal of Society of Surgeons (JSSN). He initiated Primary Trauma Care (PTC) Training in the country as the Founding Chair of PTC, Nepal. He was the Founding President of Nepal Ambulance Service (NAS), a non- profit initiative as the first proper Emergency Medical Service (EMS) with trained EMTs and a call centre accessed by calling a three-digit number 102. He is the Founding Chairperson of Hospice Nepal, the first palliative care centre in Nepal established in the year 2000. His interest in palliative care led him to Northern Ireland where he worked as fulltime trainee and completed fellowship in palliative care in 2016 under the auspices of Royal College of Physician of Edinburgh. He recently completed MSc in palliative from Ulster University. He has worked as an Instructor for HOPE (Hospital Preparedness for Emergency) Course, ‘Primary Trauma Course; and the ‘Palliative care’ courses. He has presented in numerous national and International conferences and numerous publications in national and international journals such as Palliative Medicine and has published handbooks on ‘Basic surgical skills’ and ‘Palliative care’ as well. He is an active member of the Society of surgeons of Nepal and has contributed to its establishment and development in the early days. He also served as the Chief editor of the Journal of Society of Surgeons of Nepal and has played a crucial role in the establishment of the journal encouraging scientific writing and paper publication culture amongst the fraternity. He is an important member of the society and serves as a mentor in the capacity of the advisory board of the journal.